2011
DOI: 10.1111/j.1754-9485.2011.02242.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric CT imaging trends in Australia

Abstract: The significant growth in CT services is attributable to increased demand from the adult demographic. Conversely, increases in the imaging rate for paediatric patients have slowed overall. In fact, for some age groups the rate has fallen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 23 publications
4
48
0
Order By: Relevance
“…The increase in CT and MRI usage may be attributed to a number of factors: increased staffing, technological advances leading to increased diagnostic efficacy and faster scanning times, patient-and physician-generated demand and defensive medical practices and medical uncertainty. 4,[20][21][22] Although a number of studies support our finding of an increase in the volume of CT performed in the paediatric population over time, 2,13,[17][18][19] Townsend et al 23 recently reported a reduction in the use of CT as a proportion of all cross-sectional imaging studies from 2003 to 2007 in paediatric facilities across North America. However, this study did not provide imaging rates.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The increase in CT and MRI usage may be attributed to a number of factors: increased staffing, technological advances leading to increased diagnostic efficacy and faster scanning times, patient-and physician-generated demand and defensive medical practices and medical uncertainty. 4,[20][21][22] Although a number of studies support our finding of an increase in the volume of CT performed in the paediatric population over time, 2,13,[17][18][19] Townsend et al 23 recently reported a reduction in the use of CT as a proportion of all cross-sectional imaging studies from 2003 to 2007 in paediatric facilities across North America. However, this study did not provide imaging rates.…”
Section: Discussionsupporting
confidence: 54%
“…3,13 Older studies have published national paediatric CT data from Australia, the UK, Israel and Germany. 2,[17][18][19] To date, we present the Over a 10-year period, 224,173 advanced imaging examinations were carried out, an average of 2.7 examinations per person. As expected, ultrasound was by far the most utilized modality in our study, followed by MRI, CT and NM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure is unlikely to be as low as 0 % or as high as 70 %, but it is clear that this issue is significant. Analysis of Medicare records confirms that Australian CT imaging rates are increasing, with an annual growth rate of 8.5 % [1]. Additionally, a recent international survey found that CT accounts for almost half of the collective population dose from diagnostic procedures (43 %) while constituting less than 10 % of the number of procedures performed [2].…”
mentioning
confidence: 99%
“…Pediatric CT use has increased in many countries over the last years [4,5,6,7]. However, recent data suggest that pediatric CT use may be declining in some developed countries [8,9,10].…”
Section: Introductionmentioning
confidence: 99%